Pelaksanaan Metode Casework dalam Proses Pendampingan Klien di SKA - Adzra' Vania Rahmah; Habeahan, Agustina Lena Sari; Wahyu Mei Lani; Siregar, Ibnu Khoir; Khairunnisya Rachman (Yayasan Literasi Sains Indonesia, 2023)
Social problems are long-standing problems that exist today, both in developing and developed countries. Social welfare as an institution that provides organized and systematic assistance services equipped with methods that provide assistance services to social needs both individually and in groups. This study aims to determine the method of implementing child assistance and family assistance at the Pinang Baris Children's Creativity Studio (SKA) and assistance for children facing the law at the Center for Child Protection Studies (PKPA). The type of research used is a qualitative method, and the results of the research were taken using interview techniques with several assistants in both locations, each of whom is responsible for a different field, so that we know that in the implementation of guidance as well as assistance to the need for Social Welfare Services in SKA and PKPA, there is still has a deficiency in its stages. For example, there is no contract between the client and the supervisor, then in advocacy services for children dealing with law, PKPA only gets services before and when the legal process is under way.